1992
DOI: 10.3987/com-91-s33
|View full text |Cite
|
Sign up to set email alerts
|

Use of 1,3-Dioxin-4-ones and Their Related Compounds in Synthesis. Part 35. Synthesis of Optically Pure Fluoromalonamic Acids by Means of Asymmetric Fluorination of Chiral 1,3-Oxazine-4,6-diones

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…L ‐Menthylphenyl esters of malonates were fluorinated with fluoropyridinium triflate in high yield with moderate diastereoselectivities by using lithium hexamethyldisilazane (LiHMDS). Kaneko and co‐workers also reported that fluorination of chiral 5‐substituted 1,3‐oxazine‐4,6‐dione derivatives proceeded diastereoselectively to give the 5‐fluorooxazinediones, which were readily transformed to optically pure fluoromalonic acids 8e. Sodeoka and co‐workers reported the enantioselctive fluorination of lactones and lactams, which were catalyzed by chiral palladium(II)–bisphosphine complexes 10.…”
Section: Methodsmentioning
confidence: 99%
“…L ‐Menthylphenyl esters of malonates were fluorinated with fluoropyridinium triflate in high yield with moderate diastereoselectivities by using lithium hexamethyldisilazane (LiHMDS). Kaneko and co‐workers also reported that fluorination of chiral 5‐substituted 1,3‐oxazine‐4,6‐dione derivatives proceeded diastereoselectively to give the 5‐fluorooxazinediones, which were readily transformed to optically pure fluoromalonic acids 8e. Sodeoka and co‐workers reported the enantioselctive fluorination of lactones and lactams, which were catalyzed by chiral palladium(II)–bisphosphine complexes 10.…”
Section: Methodsmentioning
confidence: 99%
“…Several examples of radical cyclization to the enamide double bond have been reported over the past few years. , Aryl radical cyclizations onto cyclic enamides generally produce heterocycles in which the nitrogen atom is present in the newly formed ring . Rigby 38 and Schultz have conducted selective 6- endo and 7- endo cyclizations of aryl radicals onto hydroindole and hydroquinoline enamide systems and have used this reaction as the key step for several alkaloid syntheses.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have been tested as inhibitors of the tumor cell growth and have exhibited the activity comparable with that for some natural pyrimidines (Scheme 8) [29,30].…”
Section: 3-oxazinesmentioning
confidence: 96%